ANALISIS KINERJA KOMISI PEMILIHAN UMUM KOTA SEMARANG (Dalam Pemilihan Umum 2014) - Desta Trianggoro; Endang Larasati; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
In a country that is implementing a democratic system such as in Indonesia, Election is implementation of popular sovereignty which aims to bring a democratic government elected by the people. To perform their duties in administration of Elections, the Commissions established as one of the organizers of Election. This study will analyze the performance of Election Commission of Semarang and the dimensions that support and hinder the performance of Election Commission of Semarang in the National Election of 2014. This study uses the theory of organization and performance of the five dimensions they are productivity, service orientation, responsiveness, responsibility, and accountability with qualitative descriptive approach. To collect the data use the technique of observation, interviews, documentation, and literature study from informant’s employees of Election Commission of Semarang. The results show the performance of Election Commission of Semarang in National Election of 2014 is not optimal yet, they found several obstacles on the dimensions of the problem of productivity such as human resources, limited budget and the socialization has not optimal yet. While the dimensions that support performance Election Commission of Semarang other already performing optimally, they are service orientation, responsiveness, responsibility, and accountability. To overcome the obstacles found, there are some suggestions that can be carried out by the Election Commission of Semarang to optimize its performance, such as education, training, and skills to improve the quality of human resources, increasing the number of human resources through the recruitment of government employees or increase the number of temporary employees, proposesincreasingthe number of budget in accordance with the needs required and improving the socialization to public intensively and regularly, not only at Election time is getting closer, but by applying democracy in everyday life.